The Analysis of SME Growth Potential in the Northern-Hungarian Region - Lukács, Edit (Theory, Methodology, Practice – Review of Business and Management, 2012)
The economic and social tendencies of the last decade’s world economy are determined by growth. Challenges like the population explosion, the growth of international enterprises’ economic role, increasing pollution, competition in innovation and the info-communicational explosion have to be faced. These tendencies provide great opportunities but also major challenges to economic actors. The purpose of this study is to summarize the theories of economic growth, to demonstrate the results of research studies that analyse the growth potential of SME and to analyse the opportunities for growth in the case of northern-Hungarian SME-s.